Evidence‐Based Strategies and Recommendations for Preservation of Central Venous Access in Children. Issue 5 (21st April 2019) - Baskin, Kevin M.; Mermel, Leonard A.; Saad, Theodore F.; Journeycake, Janna M.; Schaefer, Carrie M.; Modi, Biren P.; Vrazas, John I.; Gore, Beth; Drews, Barbie B.; Doellman, Darcy; Kocoshis, Samuel A.; Abu‐Elmagd, Kareem M.; et al.
Abstract: Children with chronic illness often require prolonged or repeated venous access. They remain at high risk for venous catheter–related complications (high‐risk patients), which largely derive from elective decisions during catheter insertion and continuing care. These complications result in progressive loss of the venous capital (patent and compliant venous pathways) necessary for delivery of life‐preserving therapies. A nonstandardized, episodic, isolated approach to venous care in these high‐need, high‐cost patients is too often the norm, imposing a disproportionate burden on affected persons and escalating costs. This state‐of‐the‐art review identifies known failure points in the current systems of venous care, details the elements of an individualized plan of care, and emphasizes a patient‐centered, multidisciplinary, collaborative, and evidence‐based approach to care in these vulnerable populations. These guidelines are intended to enable every practitioner in every practice to deliver better care and better outcomes to these patients through awareness of critical issues, anticipatory attention to meaningful components of care, and appropriate consultation or referral when necessary.*